2017
DOI: 10.3177/jnsv.63.174
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Eating Speeds Are Related to Body Composition and Shape in Female College Students

Abstract: Summary Eating speed reportedly relates to body composition and shape. Little is known about the relationship between the objectively assessed eating speed and the body composition and shape. This study examined relationships between eating speed as assessed both objectively and subjectively, and body composition and shape. The following variables of body composition and shape were measured in 84 female college students: body mass, relative body fat mass (%Fat), body mass index (BMI), and circumferences of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…The year of publication spanned from 1964 to 2020. Nine studies (one study explored both eating speed/rate and eating frequency) included only children [ 4 , 12 , 14 , 24 , 26 , 27 , 28 , 30 , 31 ] one was based on children and adolescents (≤19 years-old) [ 51 ], two articles involved only adolescents [ 25 , 29 ], four articles recruited children, adolescents and young adults [ 10 , 15 , 17 , 32 ] and finally, 36 articles included only adults [ 2 , 5 , 9 , 11 , 13 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The year of publication spanned from 1964 to 2020. Nine studies (one study explored both eating speed/rate and eating frequency) included only children [ 4 , 12 , 14 , 24 , 26 , 27 , 28 , 30 , 31 ] one was based on children and adolescents (≤19 years-old) [ 51 ], two articles involved only adolescents [ 25 , 29 ], four articles recruited children, adolescents and young adults [ 10 , 15 , 17 , 32 ] and finally, 36 articles included only adults [ 2 , 5 , 9 , 11 , 13 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Seven articles examined BMI, six looked at WC, and one assessed body weight. Hamada et al [ 53 ] studied the speed of eating, subjectively (self-reported) and objectively (total number of chews, number of chews per bite, total meal duration, number of bites, chewing rate). They observed significant inverse correlations between total number of chews and total meal duration with body weight, BMI, waist circumference and abdominal obesity [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations